A critical overview of Abuse of Power in George Orwell's Animal Farm - SEGUEDEME, ALEXIS HERGIE; ABODOHOUI, Orerien Olivier; DIKPO TOLITON, TÉLESPHORE; 1- Dr Hergie; 1- Dr Hergie (My University, 2022)
Abstract This research sets out to examine the issues of abuse of power that the whole world is facing as revealed in George Orwell’s Animal farm. Everyone today wants to lead or be on the mountain top and will do whatever to achieve that goal. This power may be related to sovereignty or the power to make rules that apply to the population of a particular area. power is certainly necessary for the development and good behaviour of everyone, but when it is today held by certain predecessors who do not want to leave room for others, there is a succession of coups d’état, megalomania and even the rebellion thus causing loss of human life causing many victims. The present article unveils from a historical satire perspective that such factors as excessive ambition, arbitrary, money, corruption and own interest are the reason why people have abuse of power.
Keywords: Keywords: Abuse; power; abuse of power; animal; animal farm